PENGARUH MANAJEMEN GEDUNG DAN STRATEGI PEMASARAN TERHADAP KEPUASAN DAN KESETIAAN PELANGGAN DIMEDIASI RENTAL PRICE - Dwi Ayu Candra; Romauli Nainggolan; Timotius Febry Christian (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Office buildings play a crucial role in supporting economic activities, particularly in business management. This research uses Plaza BRI Surabaya as a case study, given its position as an icon of Surabaya City that focuses on office space rentals with various hospitality facilities and services. In addition to understanding the operational effectiveness of building management in providing services and its impact on marketing, this research seeks to analyze the needs and preferences of businesses that wish to rent offices. This study adopts a quantitative method with surveys to collect data regarding tenant preferences, satisfaction levels, and the effectiveness of marketing strategies. Statistical analysis is used to identify patterns and relationships between variables. This research also applies a qualitative method through in-depth interviews with tenants and building managers to gain a deeper understanding of their experiences and expectations. This research is expected to contribute significantly to the development of effective and comprehensive office building rental marketing strategies. Keyword: Building Management, Office building, Marketing Strategies. Abstrak: Gedung perkantoran memainkan peran krusial dalam menunjang kegiatan ekonomi, terutama dalam pengelolaan bisnis. Penelitian ini menjadikan Plaza BRI Surabaya sebagai studi kasus, mengingat posisinya sebagai ikon Kota Surabaya yang fokus pada penyewaan ruang kantor dengan berbagai fasilitas dan layanan hospitality. Selain memahami efektivitas operasional manajemen gedung dalam pemberian layanan dan dampaknya pada pemasaran, riset ini berupaya menganalisis kebutuhan dan preferensi bisnis yang ingin menyewa kantor. Studi ini mengadopsi metode kuantitatif dengan survei untuk mengumpulkan data terkait preferensi penyewa, tingkat kepuasan, dan efektivitas strategi pemasaran. Analisis statistik digunakan untuk mengidentifikasi pola dan keterkaitan antar variabel. Penelitian ini juga menerapkan metode kualitatif melalui wawancara mendalam dengan penyewa dan pengelola gedung untuk memperoleh pemahaman yang lebih mendalam mengenai pengalaman dan harapan mereka. Riset ini diharapkan dapat berkontribusi signifikan pada pengembangan strategi pemasaran penyewaan gedung kantor yang efektif dan menyeluruh. Kata kunci: Manajemen Gedung, Gedung Perkantoran, Strategi Pemasaran.